DAMPAK GAME ONLINE MOBILE LEGENDS TERHADAP KEPRIBADIAN SOSIAL SISWA - Masrukin, Ahmad; Wasito, Wasito (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
The online game Mobile Legends has become part of the culture and daily activities of the people, especially the younger generation and even children at elementary school age. Children who often play Mobile Legends online games will reduce children's activities such as learning and interacting with peers, because online games Mobile Legends have the potential to isolate children from the social environment.This type of research is qualitative research with a case study approach, data collection techniques through interviews (interviews), observation, and documentation. The data obtained was then tested for the validity of the data through the source triangulation method, and analyzed through a qualitative descriptive analysis with three stages, namely reduction, data presentation, verification or conclusion.The results of the study, namely: (1) Children who play online games with online game types that have elements of violence can have a negative impact on the child's social personality. Most of the subjects who play online games can have an impact on their social personality, including: addiction, defiance, speaking rudely or dirty, arguing or fighting. (2) The solution to the impact of online games on the social personality of Madrasah Diniyyah Roudlotut Tholibin Bojonegoro students is what has been explained by the Head of Madrasah, teachers and parents of Madrasah Diniyyah Roudlotut Tholibin Bojonegoro students. That is, there must be an active role from the madrasah and students' parents, limiting the use of mobile phones both at the madrasa and at home, making learning fun and giving homework so that time playing online games is reduced